Green process for chlorine-free benzaldehyde from the solvent-free oxidation of benzyl alcohol with molecular oxygen over a supported nano-size gold catalyst - Choudhary, Vasant R.; Dhar, A.; Jana, Prabhas; Jha, Rani; Uphade, B. S. (Green Chemistry, 2005)
Benzyl alcohol is oxidized selectively to benzaldehyde with high yield, with a little formation of benzylbenzoate, by molecular oxygen over a reusable nano-size gold catalyst supported on U3O8, MgO, Al2O3 or ZrO2 in the absence of any solvent.